THE EARLY HISTORY OF BALINESE TRANSMIGRANTS AND THEIR COMMUNITY FORMATION STRATEGIES IN PARIGI MOUTONG, CENTRAL SULAWESI - I Ketut Gunarta; Segara, I Nyoman Yoga; Ni Kadek Apriliana; I Ketut Suparta; I Gusti Made Arya Suta Wirawan (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2026)
Basically, Balinese people do not have the ability to migrate because they are constrained by their communal-agrarian and religious system, which is collective, communal, and religious life, starting from dadia (family ties based on the male line), banjar adat (social institutions based on socio-culture, custom, and religion), and village custom. However, due to land constraints and natural disasters, they have migrated, relying on their farming skills to become successful farmers, as the Balinese people found in Parigi Moutong District, Sulawesi. How they settled in the Parigi region, then migrated to other region, and the strategies used in forming their communities are the central issues in this study. This study employs a qualitative approach, involving in-depth interviews, observation, and document analysis. Research findings indicate that the presence of Balinese people in Parigi was initially due to exile by the Dutch, who opened up new land for agriculture in Central Sulawesi. Over time, their success in land cultivation and their growing population led them to establish a social system similar to their life in Bali.